Entre a educação infantil e o ensino fundamental : uma proposta de intervenção para desencadear uma política efetiva de transição. - Corrêa, Lílian Rodrigues (2016)
This report presents the result of an intervention project that aimed to discuss about documents that guide the Early Childhood Education and Elementary Education from nine (9) years old on. It is related to the pedagogical teachers approach who worked in the last stage of the early childhood education (pre B) and in the first stage (1st year) of Elementary Education of 9 (nine) years old in order to subsidize the construction of a County Educational Policy proposal of transition between these steps. The research was addressed to the municipal Arroio Grande, County/RS, in eight schools and nineteen teachers, contemplating two methodological procedures: The intervention method itself and the method of evaluation of the intervention. The data for the evaluation were collected through observation and semi-structured interview. The intervention project was developed through eight meetings with the school teachers. The analysis of data collected in both the diagnosis and evaluation of the intervention were performed from the content analysis. From the diagnostic results emerged six categories: Playfulness x Routine; Transition as confrontational moment: either play or learn; Early childhood education: preparation for Elementary Education; pedagogical in kindergarten; literacy; teachers‟ perception in relation to the pedagogical practice on Elementary School. The intervention evaluation was conducted through qualitative approach, that came from the categories meetings and the remarks made during the intervention design and effective teachers participation that triggered the creation of a County Pedagogical Political Proposal of transition between Childhood Education and Primary Education.